Design a tacit knowledge sharing system - Al Hazza, Muataz Hazza Faizi; Hazza, Zubaidah Muataz (Design for Scientific Renaissance, 2013)
Two important major factors made the companies survive; time and cost. The minimum time that can reach the customer with minimum cost. Knowledge can be classified into two main parts: tacit knowledge and explicit knowledge. Tacit knowledge is an accumulated knowledge and more complex and more ambiguous than explicit knowledge. Sharing the knowledge will decrease the risk associated with the new development. It is the way to reduce the time and cost in the development processes. In this research we will highlight the effect of Islamic prospective on sharing the tacit knowledge. Many of working staff in any organization believe that their tacit knowledge should not be shared with others due to the lack of trust. This research aims to develop a conceptual framework for knowledge sharing from Islamic perspective. This Model is based on developing Knowledge Circles (KC) which similar to quality circles. These circles will be the source for the human information storage. This storage will guide the management to reduce the time and the cost. The roles of certain factors that influence knowledge sharing behaviour in industrial organization are Affect-based trust and shared value.